PERAN ASOSIASI PELAKU PARIWISATA INDONESIA (ASPPI) DALAM MENGEMBANGKAN PARIWISATA DI PROVINSI RIAU - Asima Rohana Sihombing; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The design of this study using qualitative method with explorative approaches. That is research of excavation. Dig to find an image of an object. Tourism has an important rule in the growth of regional progress. In this study aims to find out how the role of an organization that is Asosiasi pelaku pariwisata Indonesia ( ASPPI ) DPD Riau,in developing tourism and knowing wheter efforts through the organization’s programs have an impact to Riau Tourism. Based on the results of research conducted, there are results to show the efforts of bussiness actors in Riau especially Pekanbaru, through this association (ASPPI) already have an impact or influence for tourism development in Riau province. The program activities of this association are active in supporting the implementation of tourism development. Such as the implementation of promotional efforts in the agenda Riau Travel Mart and other tourism discussion activities. Key Word : Role, Program Effort, Tourism Development